Thermal behavior studies of solid state compounds of 4-dimethylaminocinnamylidenepyruvate with alkali earth metals, except beryllium and radium - Schnitzler, Egon; Melios, Cristo Bladimiros; Leles, Maria Inês Gonçalves; Ionashiro, Massao (Eclética Química, 2000)
Solid state compounds of general formula M(DMCP)2.nH2O, where M represents Mg, Ca, Sr, Ba, and DMCP is 4-dimethylaminocinnamylidenepyruvate, and n = 1, except for Ca, where n = 2.5, have been prepared. Thermogravimetry, derivative thermogravimetry (TG, DTG), differential scanning calorimetry (DSC), X-ray diffraction powder patterns and complexometry were used to characterize and to study the thermal decomposition of these compounds.